Implementasi Logika Fuzzy Mamdani pada Penentuan Beasiswa Peningkatan Prestasi Akademik - Musanni Fauziah Siregar (STMIK KAPUTAMA, 2020)
Scholarships are financial assistance provided to individuals intended to be used for the sake of continuing education taken. Scholarships can be given by government agencies, companies via foundations. The awarding of scholarships can be categorized as free-giving only with work ties after the completion of education. In mathematics and computer science, algorithms are sequences or steps for counting or for solving problems written by a sequence. Related, programming programming sequence or steps to solve computer programming problems. Scholarship for increasing academic achievement or abbreviated as PPA is a scholarship program from the Ministry of Research and Higher Education (Kemenrisetdikti) aimed at D3, D4, or S1 students who support education for at least 2 semesters and is specifically intended for students with pretending students whose parents can help to learn about education. In general, fuzzy systems are very suitable for penalties based on systems that address problematic problems using a mathematical model. For example, the input values and system parameters are less accurate or unclear, it is difficult to change the mathematical model. The resulting system is a unit consisting of components or elements that together provide a source of information, material, or energy to achieve a goal. This term is often used to describe a set of entities that are used, in which a mathematical model can be made.